The stabilizing effect of expanded graphite on the artificial aging of shape stabilized phase change materials. (September 2015) - Sobolčiak, Patrik; Abdelrazeq, Haneen; Ouederni, Mabrouk; Karkri, Mustapha; Al-Maadeed, Mariam A.; Krupa, Igor
Abstract: Artificial aging of Shape Stabilized Phase Change Materials (SSPCM) based on linear low density polyethylene (LLDPE) and paraffin wax (W) modified with various amounts of expanded graphite (EG) was investigated and reported in this paper. It was found that EG not only strongly suppresses leakage of paraffin wax from the material over time but also significantly improves the photo oxidation stability. The increase in the melting point of wax incorporated within LLDPE matrix during aging was observed whereas the specific melting enthalpy of the paraffin wax decreased. This is mainly caused by the leakage of paraffin wax from the blends. The melting of neat LLDPE decreased during aging whereas its specific enthalpy of melting increased. Addition of EG led to the prolonged photo-oxidation stability of materials, as confirmed by Carbonyl Index measurements.